Constraints of PT. Dyandra Promosindo Sales Division in Arranging The Indonesia International Motor Show 2023 - Irfan, Syahadam Muhamad (Journal of Indonesian Tourism and Policy Studies, 2025)
Tourism is a journey that is carried out by someone for a while and is carried out from one place to another. with tourists, business suppliers, government of tourist destinations and local communities of tourist destinations. The tourism industry is a fairly broad industry, one of the industries included in the tourism industry is the MICE industry. MICE is one of the fastest growing industries in the world. The development of MICE occurred because of the company's need to hold meetings with the aim of expanding the company's business. MICE and the tourism industry cannot be separated because the definition of MICE relates to tourism activities. An event in Indonesia that is quite well- known is the Indonesia International Motorshow. Indonesia International Motorshow is the biggest automotive event in Indonesia. IIMS has developed into the largest automotive exhibition in Indonesia, after going through a long transformation process including several name changes, GAIKINDO Auto Expo then showed extraordinary success when Dyandra Promosindo started holding the event in 2000. there are obstacles that must be faced and the organizer must prepare ways to overcome them.